Primary pulmonary adenocarcinoma manifesting as multiple metastatic-like nodules: A detailed case series analysis of two patients - Chand Trilok; Rajan Remya; Elkhazin Sana (The Journal of Association of Chest Physicians)
Primary pulmonary adenocarcinoma typically presents as diffuse alveolar opacities or mass-forming lesions. However, this study delineates two unique case reports in which patients with a background of persistent dry cough exhibited multiple bilateral pulmonary nodules on radiological imaging. These nodules, initially mimicking metastatic lesions, were ultimately identified as primary lung adenocarcinoma following extensive diagnostic evaluations. This series emphasizes the critical need for thorough diagnostic approaches in identifying atypical presentations of pulmonary adenocarcinoma.